Training, supervision and quality of care in selected integrated community case management (iCCM) programmes: A scoping review of programmatic evidence - Xavier Bosch-Capblanch; Claudine Marceau (Edinburgh University Global Health Society, 2014)
To describe the training, supervision and quality of care components of integrated Community Case Management (iCCM) programmes and to draw lessons learned from existing evaluations of those programmes